INFORMAL ASSESSMENT FOR LANGUAGE SKILLS: THE LEANERS’ PERSPECTIVE - Apsus Grumilah; Irfan Nur Aji (International Conference on Education and Language (ICEL), 2016)
Assessment is one of the important components in language teaching and learning. Through assessment, the learners’ learning achievement will be known. However, learners’ achievement cannot be accurately measured only through formal assessment which is conducted in a certain period of time with the purpose to judge of whether learners are successful or fail. In order to have accurate measurement, there should be an alternative for assessment which is conducted in ongoing process of learning. Wiggins (1998: xi) asserted that assessment should be designed to improve and educate student performance, not merely to audit as most school test currently do. Therefore, this research tried to reveal the learners’ perception as well as their preference in informal assessment. For teachers, it provides the evidence of informal assessment as an essential part in teaching and learning process. This paper is written on the basis of research which described the learners’ perception toward the use of alternative assessment in PBI UAD Yogyakarta. There were 211 randomly selected of 600 learners in language skills classes. They were asked to fill in the questionnaire to express their perception in informal assessment and to perceive the best appropriate informal assessment type for language skill.The result of the research was that learners had good perception toward the use of informal assessment. There were 67% of learners had good perception, and 26% of learners had very good perception, so there were 93% in overall of learners had good perception. In addition, about 65% of learners in all skills classes preferred the use portfolio assessment. Lastly, it was unexpectedly that learners preferred the performance assessment for listening (63.27%) and observation assessment reading (63.80%), and portfolio for speaking (70.59%) and writing (67.92%). Thus, the findings showed the high demand of learners to the practice of informal assessment for language skills.